MANAGEMENT ANALYSIS OF THE FOOD DELIVERY SYSTEM IN MEULABOH CLASS II B PRISON - Ananta Yulia Eflina; Suci Eka Putri; M. Irfan Febriansyah; Khairunnas (PT. Radja Intercontinental Publishing, 2024)
Organizing food in prisons is an institutional administration that starts from setting standards for food ingredients to distributing food. The provision of food in prisons needs to be considered because it can affect the fulfillment of inmates' intake which has an impact on nutritional and health status. The aim of this research is to analyze the management of the food delivery system in the Meulaboh Class II B prison. This research method is descriptive qualitative research. The research was conducted at the Meulaboh Class II B Prison in July – September 2023 by conducting in-depth interviews. Research informants are parties who have authority or have knowledge of something related to the management of the food delivery system in class II B prisons in Meulaboh. The number of informants in this study was 6 people, including, key informants (ik) 2 kitchen coordinators, supporting informants (ip) 2 prisoners, main informants (iu) 2 food handlers. The overall research results of the food delivery system in Meulaboh Class II B Prison do not meet standards. The process of organizing food in prisons is preparing standard food ingredients, planning menus, planning food needs, procuring food ingredients, ordering and purchasing food ingredients, receiving food ingredients, storing food ingredients, preparing food ingredients, processing food ingredients and distributing food. Suggestions for the prison to evaluate the food delivery system so that it can adapt to the established standards.